Immigration, Wages, and Compositional Amenities - David Card; Christian Dustmann; Ian Preston (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
Economists are often puzzled by the stronger public opposition to immigration than trade, since the two policies have symmetric effects on wages. Unlike trade, however, immigration changes the composition of the local population, imposing potential externalities on natives. While previous studies have focused on fiscal spillovers, a broader class of externalities arise because people value the "compositional amenities" associated with the characteristics of their neighbors and co-workers. In this paper we present a new method for quantifying the relative importance of these amenities in shaping attitudes toward immigration. We use data for 21 countries in the 2002 European Social Survey, which included a series of questions on the economic and social impacts of immigration, as well as on the desirability of increasing or reducing immigrant inflows. We find that individual attitudes toward immigration policy reflect a combination of concerns over conventional economic impacts (i.e., on wages and taxes) and compositional amenities, with substantially more weight on composition effects. Most of the difference in attitudes to immigration between more and less educated natives is attributable to heightened concerns over compositional amenities among the less-educated.
Keywords: 330